A Crystal Ball. (3rd July 2018) - Fujisaki, Ichiro
Abstract : Upon appointment as executive of Nakasone Peace Institute in the 30 th year since its establishment, NPI President Ichiro Fujisaki discusses his view of the role of a research institute and outlines the aims for NPI going forward.